Compound heterozygous variants of the NARS2 gene in siblings with refractory seizures: two case report and literature review - Wu, Heyan; Zhou, Min; Ye, Xiaoting; Chen, Huabao; Lin, Hongxin; Wang, Li; Nie, Xing; Zhang, Lidan (Frontiers in Pediatrics, 2025)
BackgroundBiallelic variants in NARS2 that encodes the mitochondrial asparaginyl-tRNA synthetase are associated with a wide spectrum of clinical phenotypes. Herein, we report on two siblings carrying the same compound heterozygous missense variants in NARS2, to improve the understanding of the phenotypic heterogeneity of NARS2 variants.Case presentationThe two probands, a 3-year-old female (Patient 1) and a 16-month-old male (Patient 2), were clinically suspected of Combined oxidative phosphorylation deficiency 24 (COXPD24). Both presented with neurological manifestations, including refractory epilepsy, developmental delay and motor developmental regression, within the first year of life, accompanied by symmetrical brain lesions identified on magnetic resonance imaging (MRI). To elucidate the underlying genetic etiology, whole-exome sequencing (WES) was performed, followed by Sanger sequencing validation in the patients and their non-consanguineous parents. Genetic analysis revealed that both probands harbored identical compound heterozygous variants in the NARS2 gene: c.1253G>A (p.Arg418His) and c.1163C>T (p.Thr388Met). Notably, the c.1163C>T (p.Thr388Met) variant in NARS2 represents a novel finding, further expanding the genetic spectrum associated with this disorder.ConclusionsOur findings expand the mutational spectrum of NARS2 and highlight the associated phenotypic heterogeneity, underscoring the critical role of NARS2 in epilepsy and neurodevelopmental processes. For pediatric patients with refractory epilepsy, early genetic testing is essential to improve diagnostic accuracy, refine prognostic stratification, and guide personalized treatment strategies. Additionally, mitochondrial drug cocktail therapy may be beneficial for epilepsy caused by NARS2 mutations.